2004
DOI: 10.1103/physrevb.70.024509
|View full text |Cite
|
Sign up to set email alerts
|

Flux-pinning properties of superconducting films with arrays of blind holes

Abstract: We performed ac susceptibility measurements to explore the vortex dynamics and the flux-pinning properties of superconducting Pb films with an array of microholes (antidots) and not fully perforated holes (blind holes). A lower ac shielding together with a smaller extension of the linear regime for the lattice of blind holes indicates that these centers provide a weaker pinning potential than antidots. Moreover, we found that the maximum number of flux quanta trapped by a pinning site, i.e., the saturation num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 19 publications
3
49
0
1
Order By: Relevance
“…Further details about sample preparation can be found in Ref. 18. In all cases the magnetic field is applied perpendicularly to the plane of the film.…”
Section: Sample Detailsmentioning
confidence: 99%
“…Further details about sample preparation can be found in Ref. 18. In all cases the magnetic field is applied perpendicularly to the plane of the film.…”
Section: Sample Detailsmentioning
confidence: 99%
“…[10][11][12] This reflects in different (according to whether or not interstitial vortices are present) scenarios of the sample response to an excitation, as indeed observed in a great deal of macroscopic ac-susceptibility experiments. [13][14][15][16][17][18][19][20][21][22] The interpretation of the different dynamical regimes usually ig-nores the random pinning potential produced by sample inhomogeneities, considered negligible at the temperatures where the experiments are carried out. However, at least for experiments performed within the linear regime, where vortices are driven close to their equilibrium positions by very small driving forces, the weak material pinning might become important or even dominant.…”
Section: And References Therein)mentioning
confidence: 99%
“…It is now well established that these artificial pinning centers (i) hold great potential for enhancing the critical parameters of the sample and (ii) give rise to different kinds of vortex behavior that is not observed in the presence of random pinning. In this respect, arrays of microholes (antidots) 1,2,3,4,5,6,7,8,9,10,11,12 and submicron magnetic dots, 13,14,15 have been studied, as their presence in the SC film strongly modifies the vortex structure compared to the one in non-patterned films. 16,17 Direct imaging experiments, 1 magnetization and transport measurements, 2,3,4,5 and theoretical simulations 18,19,20,21,22 of vortex structures in samples with periodic pinning centers have shown that the vortices form highly ordered configurations at integer H n = nΦ 0 /S and at some fractional H p/q = p q Φ 0 /S (n,p,q being integers) matching fields, where Φ 0 = hc/2e = 2.07 · 10 −7 Gcm 2 is the flux quantum, and S is the area of the primitive cell of the artificial lattice.…”
Section: Introductionmentioning
confidence: 99%
“…blind holes). 10 Most of the experiments on perforated superconducting films are carried out in the effective type-II limit (κ * = λ 2 /dξ ≫ 1/ √ 2, d being the thickness of the superconducting film and λ the magnetic penetration depth). In this regime, the vortices act like charged point particles and their interaction with periodic pinning potential can be described using molecular dynamic simulations.…”
Section: Introductionmentioning
confidence: 99%